A new ionone derivative from Lycium intricatum Boiss. (Solanaceae). Issue 3 (1st February 2022) - Bendjedou, Houaria; Maggi, Filippo; Bennaceur, Malika; Mancinelli, Michele; Benamar, Houari; Barboni, Luciano
Abstract: Lycium intricatum Boiss also called 'Awsadj' is a subshrub belonging to the Solanaceae family and producing red berries. In the present work, we report the isolation of a new compound, ((1 R, 3aR, 7aS)-3a, 7-dimethyl-1-((E)-prop-1-en-1-yl)-1, 3a, 4, 7a-tetrahydroisobenzofuran-5(3H)-one (1 )). Three known compounds were also isolated for the first time from L. intricatum, and identified as isoscopoletin (2), 3, 4, 5-trimethoxybenzyl alcohol (3 ), and (+)-isolariciresinol (4 ). Compounds 1 -4 were isolated from the extract of leaves using chromatographic techniques, and the structure of compound 1 was fully elucidated by NMR, MS and ECD experiments. Graphical Abstract: